Carrots and sticks vs carrots: Comparing approaches to workplace travel plans using disincentives for driving and incentives for active travel. Issue 4 (December 2015) - Petrunoff, Nick; Rissel, Chris; Wen, Li Ming; Martin, Jacob
Abstract: Background: A natural experiment became evident in Perth, Western Australia, where two adjoining hospitals–Queen Elizabeth II Medical Centre and Hollywood Private Hospital–conducted staff surveys to evaluate travel plans at the same time using similar methods. Purpose: We compared the results from two travel plans as a retrospective, controlled, before–after study in 2006 and 2012, to inform the development of active travel plans. Methods: Reports describing the staff surveys conducted at the two adjoining sites in 2006 and 2012 were reviewed to assess data comparability. Staff travel surveys were conducted at both sites at approximately the same time in 2006 and 2012. A Chi-squared test was conducted to assess the difference in two proportions for staff driving alone at both sites in 2006 and 2012. Descriptive statistics of the staff travel mode split at the two sites were located and were summarised for comparison. Results: It was found that there was a 42% reduction in driving alone amongst QEII Medical Centre staff and a 5% reduction in driving alone amongst Hollywood Private Hospital staff. A 37% difference in the reduction of staff driving to work alone between the two sites was significant ( X 2 =87.5; P <0.001). Conclusions: The present study is unique in being able to compare two travel plans using reasonably well matched sites. A workplace travel plan including parking management strategies to complement strategies to encourage active and sustainable forms of travel to work, may be more effective than a travel plan that includes encouragement strategies alone. Evaluations of travel plans with robust study designs such as controlled before–after studies and cluster-randomised controlled trials (cluster-RCTs) are needed to provide stronger evidence, and pragmatic approaches to implementing controlled trials will need to be considered. Studies exploring the acceptability of parking management strategies are also needed.